Inflammation and Mechanical Stress Stimulate Osteogenic Differentiation of Human Aortic Valve Interstitial Cells - Bogdanova, Maria; Kostina, Aleksandra; Zihlavnikova Enayati, Katarina; Zabirnyk, Arsenii; Malashicheva, Anna; Stensløkken, Kåre-Olav; Sullivan, Gareth John; Kaljusto, Mari-Liis; Kvitting, John-Peder Escobar; Kostareva, Anna; Vaage, Jarle; Rutkovskiy, Arkady (Frontiers in Physiology, 2018)
Background: Aortic valve calcification is an active proliferative process, where interstitial cells of the valve transform into either myofibroblasts or osteoblast-like cells causing valve deformation, thickening of cusps and finally stenosis. This process may be triggered by several factors including inflammation, mechanical stress or interaction of cells with certain components of extracellular matrix. The matrix is different on the two sides of the valve leaflets. We hypothesize that inflammation and mechanical stress stimulate osteogenic differentiation of human aortic valve interstitial cells (VICs) and this may depend on the side of the leaflet. Methods: Interstitial cells isolated from healthy and calcified human aortic valves were cultured on collagen or elastin coated plates with flexible bottoms, simulating the matrix on the aortic and ventricular side of the valve leaflets, respectively. The cells were subjected to 10% stretch at 1 Hz (FlexCell bioreactor) or treated with 0.1 μg/ml lipopolysaccharide, or both during 24 hours. Gene expression of myofibroblast- and osteoblast-specific genes was analyzed by qPCR. VICs cultured in presence of osteogenic medium together with lipopolysaccharide, 10% stretch or both for 14 days were stained for calcification using Alizarin Red. Results: Treatment with lipopolysaccharide increased expression of osteogenic gene bone morphogenetic protein 2 (BMP2) (5 fold increase from control; p=0.02) and decreased expression of mRNA of myofibroblastic markers: α-smooth muscle actin (ACTA2) (50% reduction from control; p=0.0006) and calponin (CNN1) (80% reduction from control; p=0.0001) when cells from calcified valves were cultured on collagen, but not on elastin. Mechanical stretch of VICs cultured on collagen augmented the effect of lipopolysaccharide. Expression of periostin (POSTN) was inhibited in cells from calcified donors after treatment with lipopolysaccharide on collagen (70% reduction from control, p=0.001), but not on elastin. Lipopolysaccharide and stretch both enhanced the pro-calcific effect of osteogenic medium, further increasing the effect when combined for cells cultured on collagen, but not on elastin. Conclusion: Inflammation and mechanical stress trigger expression of osteogenic genes in VICs in a side-specific manner, while inhibiting the myofibroblastic pathway. Stretch and lipopolysaccharide synergistically increase calcification.